The growth and characterization of GaN films on cone-shaped patterned sapphire by MOCVD - 井亮 肖红领 王晓亮 王翠梅 邓庆文 李志东 丁杰钦 王占国 侯洵 (Journal of semiconductors, 2013)
GaN films are grown on cone-shaped patterned sapphire substrates （CPSSs） by metal-organic chemical vapor deposition, and the influence of the temperature during the middle stage of GaN growth on the threading dislocation （TD） density of GaN is investigated. High-resolution X-ray diffraction （XRD） and cathodeluminescence （CL） were used to characterize the GaN films. The XRD results showed that the edge-type dislocation density of GaN grown on CPSS is remarkably reduced compared to that of GaN grown on conventional sapphire substrates （CSSs）. Furthermore, when the growth temperature in the middle stage of GaN grown on CPSS decreases, the full width at half maximum of the asymmetry （102） plane of GaN is reduced. This reduction is attributed to the enhancement of vertical growth in the middle stage with a more triangular-like shape and the bending of TDs. The CL intensity spatial mapping results also showed the superior optical properties of GaN grown on CPSS to those of GaN on CSS, and that the density of dark spots of GaN grown on CPSS induced by nonradiative recombination is reduced when the growth temperature in the middle stage decreases.